The Misnomer of Nomarchs: Οἱ νομάρχαι and Provincial Administrators of the Old-Middle Kingdoms - Tomkins, Jessica (Zeitschrift für ägyptische Sprache und Altertumskunde, 2018)
The terms “nome” and “nomarch” are widely used in Egyptology as the basic framework for discussing and understanding provincial administration of the Old to Middle Kingdoms, even though these are much later Greek terms. This article traces the origins of these words and highlights the problems encountered by applying these later terms to an earlier period of Egyptian history, and how they have obscured our understanding of the mechanics of provincial administration of the Old to Middle Kingdoms.